Tác động của nhận thức trách nhiệm xã hội điểm đến du lịch đến hành vi xã hội của người lao động trong lĩnh vực khách sạn tại Việt Nam - Hoàng Trọng, Hùng; Hồ Thị Thúy , Nga; Mai Thị Kiều , Lan; Trần Hà Uyên , Thi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The purpose of this study is to examine the impact of perceived Destination Social Responsibility the social behavior of employees working in 4- and 5-star hotels in Vietnam. Based on the social identity theory, a survey of employees working in 4- and 5-star hotels in Vietnam, and using a structural equation model, the results show that Destination Social Responsibility has a positive impact on employees’ social behavior. Destination Social Responsibility also has a positive impact on organizational identification, and organizational identification has a positive impact on destination identification, thereby affecting social behavior. However, this study does not find a significant direct relationship between organizational identification and social behavior. Based on the research results, some managerial implications to promote the social behavior of hotel employees are provided.